Polyhydroxybutyrate production by an extremely halotolerant Halomonas elongata strain isolated from the hypersaline meromictic Fără Fund Lake (Transylvanian Basin, Romania) - Cristea, A; Baricz, A; Leopold, N; Floare, C G; Borodi, G; Kacso, I; Tripon, S; Bulzu, P A; Andrei, A-Ș; Cadar, O; Levei, E A; Banciu, H L (Journal of applied microbiology, 2018)
AIM: This study aimed at unprecedented physical and chemical evaluation of the 'green plastics' polyhydroxyalkanoates (PHAs), in an extremely halotolerant Halomonas elongata strain 2FF under high-salt concentration. METHODS AND RESULTS: The investigated bacterial strain was isolated from the surface water of the hypersaline Fără Fund Lake. The 16S rRNA gene sequence phylogeny and phenotypic analysis indicated that the isolate belonged to H. elongata. PHA inclusions were observed by Sudan Black B, Nile Red staining, and transmission electron microscopy during growth at high salinity (10%, w/v, NaCl) on 1% (w/v) d-glucose. The produced polymer was quantitatively and qualitatively assessed using crotonic acid assay, elemental analysis, Fourier transform infrared and Raman spectroscopies. Additionally, X-ray powder diffraction, 1 H-NMR spectroscopy, and differential scanning calorimetry were applied. The investigations showed that the intracellular polymer was polyhydroxybutyrate (PHB) of which the strain produced up to 40 wt% of total cell dry weight after 48 h. The analysis of phaC gene from the isolated H. elongata strain indicated that the encoded PHA synthase belongs to Class I PHA synthase family. CONCLUSIONS: Overall, our investigations pointed out that the halotolerant H. elongata strain 2FF was capable to produce significant amounts of PHB from d-glucose, and PHAs from various carbon substrates at high-salt concentrations. SIGNIFICANCE AND IMPACT OF THE STUDY: The tested strain showed the ability for significant production of natural, biodegradable polymers under nutrient limitation and hypersaline conditions suggesting its potentiality for further metabolic and molecular investigations towards enhanced biopolymer production. Additionally, this study reports on the unprecedented use of Raman and XPRD techniques to investigate PHAs of an extremely halotolerant bacterium, thus expanding the repertoire of physical methods to study green plastics derived from extremophilic microorganisms.
Keywords: green plastics; Sodium Chloride; Rumunsko; Romania; polyhydroxyalkanoáty; jezera; chlorid sodný; RNA, Ribosomal, 16S; biopolymery; Halomonas; Halomonas sp.; high salinity; polyhydroxybutyrate; Phylogeny; nutrient limitation; Biopolymers; halotolerant bacteria; Lakes; fylogeneze; Polyhydroxyalkanoates; RNA ribozomální 16S